(untitled) (Revista Innova Educación, 2024)
Psychopedagogical strategies are crucial for enhancing linguistic progress in students, promoting communicative skills, and overcoming difficulties. The article aims to develop a psychopedagogical strategy to improve language development in students at the Portoviejo Educational Unit who have been affected by domestic violence. The methodology employed is a mixed-method, descriptive, non-experimental approach. The theoretical methods used were analytical, inductive-deductive, while the techniques included surveys of teachers, language development assessment tests using the Instrument for School Age (IDTEL), as well as interviews with experts. The intentional population and sample consisted of 7 students aged 6 to 9 affected by domestic violence, 12 teachers from these educational levels, and 3 experts knowledgeable about the topic. The results highlight the difficulties experienced by students affected by domestic violence in their language development and usage. 61% exhibit low levels in morphosyntactic aspects, 69% in pragmatic aspects, 51% in phonological aspects, and 52% in semantic aspects. The article concludes with the design of a psychopedagogical strategy aimed at improving language development in students affected by domestic violence through activities that promote confidence, self-esteem, listening comprehension, expression, and literacy skills. This strategy was validated by experts in the field, endorsing its viability and the importance of addressing the linguistic difficulties of these students.